2020
DOI: 10.1177/0898264319895842
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Medications With Cognitive Impairment Side Effects and the Implications for Older Adults’ Cognitive Function

Abstract: Objectives: Many medications have cognitive impairment, memory loss, amnesia, or dementia as side effects (“cognitive side effects” hereafter), but little is known about trends in the prevalence of these medications or their implications for population-level cognitive impairment. Method: We use data from the National Health and Nutrition Examination Survey (1999–2016) to describe trends in the use of medications with cognitive side effects among adults aged 60+ ( N = 16,937) and their implications for cognitiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Furthermore, medications commonly used to treat many chronic conditions can have cognitive side effects, particularly in older adults [ 65 , 66 ]. The prevalence of taking multiple medications has dramatically increased in the past two decades: an over 50% increase in older adults taking two, and an almost 300% increase in those taking three or more [ 67 ]. Future research on SCD, multimorbidity, and AD risk should consider the potential role of medications and polypharmacy on cognitive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, medications commonly used to treat many chronic conditions can have cognitive side effects, particularly in older adults [ 65 , 66 ]. The prevalence of taking multiple medications has dramatically increased in the past two decades: an over 50% increase in older adults taking two, and an almost 300% increase in those taking three or more [ 67 ]. Future research on SCD, multimorbidity, and AD risk should consider the potential role of medications and polypharmacy on cognitive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have documented the negative health consequences of polypharmacy, including adverse drug events, drug–drug interactions, medication non‐adherence, falls and cognitive impairment (Fulton & Riley Allen, 2005). Polypharmacy may present unique risks for medication side effects, amplifying the effects of each of the medications in a set (Do & Schnittker, 2020). Further, polypharmacy may increase the risk of drug–drug interactions that may result in insomnia symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Qato, Ozenberger, and Olfson (2018) used a nationally representative sample of US adults from the National Health and Nutrition Examination Survey (NHANES) and found that respondents who simultaneously consumed at least three medications with depression side effects were 10.7 percentage points more likely to report depressive symptoms compared to non‐users. Using the same survey, Do and Schnittker (2020) reported that the concurrent use of three or more medications with cognitive impairment side effects among US older adults increased 3‐fold between 1999 and 2016. In addition, individuals who used three or more such medications experienced increased risks of cognitive deficits compared to non‐users.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations